2022
DOI: 10.4193/rhin22.117
|View full text |Cite
|
Sign up to set email alerts
|

Sleep impairment in patients with empty nose syndrome

Abstract: Background: Empty nose syndrome (ENS) is characterized by paradoxical nasal obstruction that usually occurs after turbinate surgery. Patients with ENS may also experience significant psychiatric symptoms and sleep dysfunction, which negatively affect the quality of life of affected subjects. This study aimed to evaluate sleep impairment and sleepiness in patients with ENS. Methods: Patients with ENS and control participants were recruited prospectively. The Sino-Nasal Outcome Test-25 (SNOT-25), Empty Nose Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Patients with ENS usually carry a substantial psychological burden and experience significant sleep dysfunction. [2][3][4] Previous studies have demonstrated that depression and anxiety are prevalent in patients with ENS and could be predictors of surgical outcomes and residual disease. the EpSS and MSQI in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with ENS usually carry a substantial psychological burden and experience significant sleep dysfunction. [2][3][4] Previous studies have demonstrated that depression and anxiety are prevalent in patients with ENS and could be predictors of surgical outcomes and residual disease. the EpSS and MSQI in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The Empty Nose Syndrome 6-item Questionnaire (ENS6Q), Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), Epworth Sleepiness Scale (EpSS), and modified sleep quality index (MSQI) were used to measure the severity of symptoms, psychological burden (depression and anxiety), and sleep quality before and 6 months after surgery. 2,3 Data are shown as mean ± standard deviation (SD) and were statistically analyzed. Perioperative measurements were compared and analyzed using the Wilcoxon signedrank test and Pearson's correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations